Las habilidades lectoras y su incidencia en el proceso de enseñanza aprendizaje del idioma inglés en los estudiantes del noveno año, sección matutina, de la unidad educativa Eugenio Espejo del cantón Babahoyo, provincia de los ríos, periodo lectivo 2015 - 2016 - Bastidas Solís, Angélica Fabiola (2016)
Given the recognition that the English language has as a means of international communication, all educational systems of countries that do not recognize the validity of the study of this language as a second language for communication. Therefore, countries that make extensive this recognition include within their educational systems as part of the curriculum from elementary school, secondary education and especially higher education; in this way it is understood to be part of the curriculum of study at different educational levels. Once the diagnosis, we proceeded to the development of various reading strategies such as brainstorming, the ability to use the context of the sentence to make inferences and predictions, obtaining the general idea of the text through quick readings ( skimming) and the idea or supporting ideas and details (scanning), the use of the dictionary, the riddle of unknown words using context, and the use of indicators. The texts to implement the aforementioned strategies were selected by the facilitator of the subject who took note reading skills and their impact on the teaching and learning of English language students in the ninth year, morning section of the educational unit Eugenio Espejo canton Babahoyo, Los Rios province.